2001
DOI: 10.1080/10473289.2001.10464251
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure Levels and Microenvironmental Concentrations of Formaldehyde and Acetaldehyde in the Helsinki Metropolitan Area, Finland

Abstract: Personal 48-hr exposures to formaldehyde and acetaldehyde of 15 randomly selected participants were measured during the summer/autumn of 1997 using Sep-Pak DNPH-Silica cartridges as a part of the EXPOLIS study in Helsinki, Finland. In addition to personal exposures, simultaneous measurements of microenvironmental concentrations were conducted at each participant's residence (indoor and outdoor) and workplace. Mean personal exposure levels were 21.4 ppb for formaldehyde and 7.9 ppb for acetaldehyde. Personal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
33
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 19 publications
13
33
3
Order By: Relevance
“…The personal exposure concentrations reported here are also lower than those reported in overseas studies conducted on adults (Jurvelin et al 2001;Gustafson et al 2005). This finding is consistent with personal exposure studies and ambient air monitoring for other pollutants, with concentrations in Australian studies reported to be lower than overseas ( 46% of homes less than 10 years old.…”
Section: Comparison With Australian and International Datasupporting
confidence: 72%
See 1 more Smart Citation
“…The personal exposure concentrations reported here are also lower than those reported in overseas studies conducted on adults (Jurvelin et al 2001;Gustafson et al 2005). This finding is consistent with personal exposure studies and ambient air monitoring for other pollutants, with concentrations in Australian studies reported to be lower than overseas ( 46% of homes less than 10 years old.…”
Section: Comparison With Australian and International Datasupporting
confidence: 72%
“…This has been found to be a significant factor impacting on indoor concentrations of formaldehyde or emissions from formaldehyde containing materials (Godish 1990;Garrett et al 1997;Brown 1999;Jurvelin et al 2001;Gustafson et al 2005) and is hence expected to impact on personal exposure. The ability to identify seasonal variation in personal exposure was limited by the mild meteorological conditions experienced during both winter and summer sampling (Section 3.3).…”
Section: Seasonal Variation In Personal Exposurementioning
confidence: 99%
“…The median indoor/outdoor ratios for compounds typically associated with traffic emissions and long-range transport of pollutants exceeded 1, in some cases quite considerably, indicating substantial indoor source contributions. Jurvelin et al (2001b) analyzed a carbonyl data set collected in EXPOLIS-Helsinki besides the standard EX-POLIS measurements. Using Sep-Pak DNPH-Silica cartridges, formaldehyde and acetaldehyde exposures and concentrations in the standard EXPOLIS microenvironments were measured for 15 subjects.…”
Section: Vocmentioning
confidence: 99%
“…Jurvelin et al 9) reported an interesting data that the mean indoor residential concentration of HCHO in the Helsinki metropolitan area was higher than the mean workplace concentration in Finland, and that personal exposure level was mainly influenced by residential exposure. Our field study was performed in residential rooms in houses ranging from 0.01 to 25 years old ( Table 1).…”
Section: Discussionmentioning
confidence: 99%